Spontaneous ovulation and pregnancy in women with polycystic ovarian disease; a cross sectional study - Sleem, Mostafa A.; Mohamed, Ibrahim I.; Zakherah, Mahmoud S.; Abbas, Ahmed M.; Kamel, Momen A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Polycystic ovary disease (PCOD) is the most common endocrine disorder in women of reproductive age, with a prevalence of approximately 5-10%. This study aims to assess the rate of spontaneous ovulation and pregnancy in patients. The present study was a cross sectional study conducted at Woman's Health Hospital, Assiut University, Assiut, Egypt. Methods: The current study was a cross sectional study carried out in Assiut Women's Health Hospital between the 1st October 2016 and 31st July 2017. The patients were selected as infertile patients with PCOD. The patient ages range between 20 and 35 years. The BMI is between 18 and 30 Kg/m2. The main outcome measure was the rate of spontaneous ovulation and spontaneous pregnancy in the 3 cycles. Results: The mean age of the study participants was 26.64±4.59 years and the mean BMI was 24.46±2.62Kg/m2. The sonographic ovarian volume was 12.47±0.69 mm3 for the right ovary and 12.74±0.73 mm3 for the left ovary. No difference in the serum FSH, LH, FSH/LH ratio and prolactin over the 3 consecutive cycles. The rate of spontaneous ovulation in the 3 cycles was 6 women (8.6%) and 2 cases (2.8%) became pregnant spontaneously during the study period. There is no statistical significant difference between ovulating and non-ovulating women according to the BMI and ovarian volume. Conclusions: The present study concluded that the rate of spontaneous ovulation was 8.6% in women with PCOD within 3 cycles with no adverse effects of drugs or surgical interference.